RESPON PERTUMBUHAN BIBIT DURIAN (Durio zibethinus L) AKIBAT PEMBERIAN KOMPOS DAUN KERING DAN PUPUK ORGANIK CAIR TOP G2 - roni, Roni Griono Laia; Indra Purnama; Endriani (UIR Press, 2025)
Durian (Durio zibethinus Murr.) is an exotic tropical fruit with a unique taste and aroma. Durian fruit, also called the king of fruits, is very popular among various communities for its distinctive taste. Vegetative propagation techniques used by farmers remain less efficient, both in terms of time and implementation, so the ability to provide superior durian seeds remains limited, and the price is relatively high. One technique involves using compost and liquid organic fertilizer TOP G2, which also helps rehabilitate, improve, and maintain the fertility of cultivated land, thereby significantly increasing plant growth and quality. This research was conducted experimentally using a Completely Randomized Design (CRD) factorial with two factors: K (dry leaf compost) with 3 levels and T (POC TOP G2) with 3 levels, each with 3 replications. The number of experimental units is 27 plots. Each plot consists of 4 plants, with 1 plant as a sample, for a total of 27 × 4 = 108 plants. The analysis of variance showed that providing dry leaf compost and POC TOP G2 had a significant effect on the observation parameters of stem diameter, leaf length, and leaf width but had no significant effect on plant height or leaf number. The results of the best further treatment tests were in the K2T2 treatment (provision of dry leaf compost 2 kg/plant and provision of POC TOP G2 10 cc/l plant) and K1T2 (provision of dry leaf compost 1 kg/plant and POC TOP G2 10 cc/l plant). The lowest treatment was K0T0 (without the provision of dry leaf compost and POC TOP G2).